Integrasi Artificial Intelligence dalam Sistem Manajemen Pendidikan Islam untuk Meningkatkan Efisiensi Administrasi - Pohan, Rahmadanni; Pohan, Nurmaliana (Ali Institute or Research and Publication, 2025)
Islamic educational institutions such as madrasas often experience delays and data errors in grade processing and report preparation because administrative processes are still carried out manually. This study aims to automate grade recaps and academic report generation by applying artificial intelligence (AI) to improve the efficiency and accuracy of educational management. The methods used include needs analysis in one Islamic high school (MA), AI-based system design, and implementation of a machine learning module for grade analysis. This trial was conducted in one Madrasah Aliyah (MA) with 150 student grade records collected between July and December 2024 and 20 teaching and education staff. The test results showed that the average grade recap time was reduced from approximately 2–3 days to only 8–10 minutes (≈97%), academic report generation from 3–5 days to 1–2 hours, and the input error rate decreased by more than 90%. A total of 85% of teaching and administrative staff stated that the system was very helpful in their work. These findings confirm that AI integration significantly improves the efficiency, accuracy, and transparency of Islamic educational administration while making an important contribution to the madrasah digitalization agenda. This research is expected to make a tangible contribution to the digitalization of Islamic education through the use of AI technology. Although the prototype was demonstrated at a single institution, its modular architecture illustrates a novel adaptation of AI in Islamic educational administration.